A educação do campo em Itauna (MG): uma escola em construção - Silva, Tânia Mara de Andrade Oliveira e (2019)
This dissertation adresses the Country School in current days, a school built by those who take part init. To unveil the redefinition of the Rural School into Country School is not an easy task as the Rural School is still a term used by some teachers. My interest in the study of the academic formation of the teachers of the Country School had personal and professional motivation and both very important as I am a teacher’s daughter and also in every day contact with teachers from the Country School. The object of this study is the reflection on the academic formation of teachers from a Country School in Itaúna MG and the most suitable configuration of their formation and also the relationship between the school and the community where it is located. The general objective of this study is to understand the academic formation of these teachers who work at the Country school and how the community where it is located understand it. The subjects of this research are: five teachers of junior hight-school (initial years), two teachers from kindergarden , the principal of the school, one pedagogue and also forty-three parents of the children from the kindergarten and junior hight-school. The approach used was the qualitative research with the use of semi-structured questionnaire and analysis of data from “Análise de Conteúdo de Bardini (2004). The research was based on the concepts of rural education and country education as well as the hystorical context, public policies, curriculum, legal instruments, academic formation of the teachers. Some authors who dedicate thenselves to the study of the academic Apple (2006), Abramowicz (1996,2001,2016), Arroyo (1999, 2002, 2004, 2007, 2011), Caldart (2011), Fernandes (1999, 2004), Nóvoa (1995, 2002, 2017), Noffs (2013, 2016, 2018, 2019), Freire (1991, 1996, 1997, 2001), Feldmann (2009), Moreira e Silva (1995), Ghedin (2006, 2012), Silva (2011) and the study of documents that refer to the theme “country education”. This study enable the inference that the academic formation and the teaching practice in the great majority of the country schools are rooted in urban traits which is seeing in the institution object of this research. It is necessary to re-signify the formation process for the country school based on its actors, their context, their needs and their possibilities of transformation. It’s necessary to think about the Country School having its peculiar traits as the basic of its construction